2022
DOI: 10.3390/ijerph19053102
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Experiences during the COVID-19 Pandemic—A Cross-Sectional Study from Norway

Abstract: The purpose of this cross-sectional study was to map dental students’ experience of the study situation throughout the pandemic. All clinical dental students (year 3 to 5) at the Faculty of Medicine, Department of Clinical Dentistry (IKO), University of Bergen (UiB), Norway, were invited. Participation was anonymous and voluntary, and the response rate was 63%. Questions regarding stress-related factors were divided into three categories. In the category «Stressors/learning», a statistically significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…These results imply that these factors, probably not alone, have contributed to the thought of dropping out in this group of students. Students usually feel aggravated anxiety in the course of outbreaks and pandemics (Gurgel et al, 2020;Løset et al, 2022). This anxiety, which is even more intense in clinical students (Wong et al, 2004;Løset et al, 2022), might impact both their daily lives and career plans directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results imply that these factors, probably not alone, have contributed to the thought of dropping out in this group of students. Students usually feel aggravated anxiety in the course of outbreaks and pandemics (Gurgel et al, 2020;Løset et al, 2022). This anxiety, which is even more intense in clinical students (Wong et al, 2004;Løset et al, 2022), might impact both their daily lives and career plans directly.…”
Section: Discussionmentioning
confidence: 99%
“…Students usually feel aggravated anxiety in the course of outbreaks and pandemics (Gurgel et al, 2020;Løset et al, 2022). This anxiety, which is even more intense in clinical students (Wong et al, 2004;Løset et al, 2022), might impact both their daily lives and career plans directly. Among the clinical students that had thoughts of dropping out of dental education in this study, the ratio of those that were in search of a dental specialty requiring less close contact while treating patients due to the COVID-19 pandemic was signi cantly higher than the rest, which may also be the attributed to the increased level of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that numerous studies [ 7 , 8 , 9 ] have distinguished between the wellbeing of various student populations within the broad undergraduate student population. These studies have indicated dissimilarities in student populations relating to gender differences, field of study and year of education.…”
Section: Introductionmentioning
confidence: 99%
“…The complexities of the wellbeing of students in the health sciences have, for instance, been especially pertinent. In a study that mapped the complex experiences of dental students in years three to five [ 8 ], women were found to be significantly more stressed due to a lack of clinical skills ( p = 0.048). The study also highlighted elevated stress levels due to a lack of existing clinical skills ( p = 0.012) and challenges in terms of being able to complete the required clinical skills courses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation